(untitled) (American Journal of Technology and Applied Sciences, 2024)
In this article, the implementation of the corporate management system in joint-stock companies of Uzbekistan, as well as the development of proposals and recommendations for the improvement of the corporate management system in the activities of joint-stock companies.